2004
DOI: 10.1002/eat.10267
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation into the feasibility and efficacy of a CD‐ROM–based cognitive‐behavioral self‐help intervention for bulimia nervosa

Abstract: This intervention has potential as a first step in the treatment of bulimia nervosa and for dissemination to nonspecialist settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 21 publications
1
39
0
2
Order By: Relevance
“…The open trials of self-help for BN or EDNOS [3][4][5][6][7][8][9] ( 21 also reported positive outcomes, with five of seven completers ceasing binge eating or demonstrating a clinically significant reduction in binge eating, suggesting a potential utility for self-help interventions.…”
Section: Resultsmentioning
confidence: 88%
“…The open trials of self-help for BN or EDNOS [3][4][5][6][7][8][9] ( 21 also reported positive outcomes, with five of seven completers ceasing binge eating or demonstrating a clinically significant reduction in binge eating, suggesting a potential utility for self-help interventions.…”
Section: Resultsmentioning
confidence: 88%
“…For example, investigators are testing a computer-augmented cognitive-behavioral therapy for panic disorder 42 and a CD-ROM-based self-help treatment for BN. 43 Activity monitors to keep track of physical activity, handheld devices with software to monitor and analyze nutrition information, and tailored computer-made health communications or computer-delivered treatment components using clinic-based kiosks, are being used in weight loss, health care, and lifestyle interventions. [44][45][46] Given that binge eating occurs within the context of both increased negative affect and physical hunger, research needs to examine aspects of each of these as causal factors in initiating and maintaining binge episodes, as well as to replicate studies indicating that BED individuals can be divided into dieting and dieting/negative affect subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…For example, CD-ROM and web-based programmes have been shown to reduce anxiety and increase knowledge prior to aesthetic breast reduction (Danino et al, 2005), increase knowledge of self-regulation and self-efficacy in children with asthma (Shegog et al, 2001), increase daily intake of fruits and vegetables (Block et al, 2004) and increase self-efficacy and knowledge about both low-fat and infant feeding in women receiving food assistance (Campbell et al, 2004). In addition, pilot studies using computerised psychoeducation for anorexia nervosa (Andrewes et al, 1996), web-based treatment for students at risk for eating disorders (Winzelberg et al, 1998(Winzelberg et al, , 2000Zabinski et al, 2001), and CD-ROM for BN (Bara-Carril et al, 2004) have all found promising results. Finally, web-based behavioural weight loss treatment resulted in greater weight loss relative to web-based internet education (Tate, Wing, & Winett, 2001) and adding a behavioural e-counselling component to an internet weight loss intervention significantly improved weight loss in adults at risk for diabetes (Tate, Jackvony, & Wing, 2003).…”
Section: Introductionmentioning
confidence: 97%